Maize yield response to nitrogen in Malawi’s smallholder production systems - Snapp, Sieglinde S.; Jayne, Thomas S.; Mhango, Wezi; Benson, Todd; Ricker-Gilbert, Jacob (International Food Policy Research Institute, 2014)
This paper has two objectives. Our first objective is to review the research evidence on the factors known to be affecting the efficiency with which Malawian farmers use nitrogen fertilizer on maize. It is our position that such factors, along with non-random aspects of most trials, might explain the large gaps observed between researcher-managed plots and farmer-managed fields. Our second objective is to provide practical guidance to Malawian policy makers and the national extension sys-tem for helping farmers to raise the efficiency with which they use fertilizer. In so doing, we emphasize that crop diversifi-cation and soil management practices that raise soil fertility, while often viewed as “alternative” forms of agriculture, may be more accurately characterized as major components of an input-intensive and efficient production system that is both profitable and sustainable.